2020
DOI: 10.1530/ec-19-0515
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine metabolism in the proliferation of GS-expression pituitary tumor cells

Abstract: Objective: Many cancer cells cannot survive without exogenous glutamine (Gln); however, cancer cells expressing glutamine synthetase (GS) do not have this restriction. Previous metabolomics studies have indicated that glutamine metabolism is altered during pituitary tumorigenesis. However, the main role of Gln in pituitary adenoma (PA) pathophysiology remains unknown. The aim of this study was to evaluate the expression of GS and the main role of Gln in human PAs. Methods: We used cell proliferation assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…19,20 A study performed on animal cell cultures was removed. 21 A study that investigated PAs without specifying which of those had GH hypersecretion was excluded. 22 Three studies that evaluated duplicate groups of patients were removed.…”
Section: Literature Searchmentioning
confidence: 99%
“…19,20 A study performed on animal cell cultures was removed. 21 A study that investigated PAs without specifying which of those had GH hypersecretion was excluded. 22 Three studies that evaluated duplicate groups of patients were removed.…”
Section: Literature Searchmentioning
confidence: 99%
“…Glutamate is also involved in glutathione (GSH) synthesis, which is a predominant antioxidant enzyme that protects cancer cells from various oxidative stresses such as chemotherapy and radiation [ 12 15 ]. Based on the essential roles of glutamine in cancer cell homeostasis, it has been reported that many cancer cells such as lung adenocarcinoma; acute myeloid leukemia; breast; liver; and brain cancer are vulnerable to glutamine deprivation stress, suggesting the crucial role of glutamine in modulating cancer cell survival [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptiomics data ( 6 ) and metabolomics investigations ( 7 ) supported the potential oncogenetic roles of metabolic dysregulation in PAs. Our group has reported that dysregulated glucose metabolism ( 8 ), cholesterol metabolism ( 9 ) and glutamine metabolism ( 10 ) might play important roles in the tumorigenesis of PAs. For example, we have reported that lactate dehydrogenase A (LDHA) enhances the glycolysis in pituitary GH3 cells, and then promotes the invasion and proliferation of GH3 cells ( 8 ).…”
Section: Introductionmentioning
confidence: 99%